Behavior of ionophore antibiotics in aquatic environments in Argentina: The distribution on different scales in water courses and the role of wetlands in depuration. (December 2019) - Alonso, Lucas L.; Demetrio, Pablo M.; Capparelli, Alberto L.; Marino, Damián J.G.
Abstract: We studied for the first time three ionophore anticoccidial drugs: monensin (MON), lasalocid (LAS), and salinomycin (SAL) as emerging pollutants originating from animal and plant husbandry in surface waters (n = 89) in one of the most extensive hydrological basins in South América (Del Plata basin). The soluble fraction of ionophores was pretreated by solid-phase extraction and analyzed by LC-MS/MS at a limit of detection of 1.7 ng·L −1 . A statistical approach noted the need to report parameters calculated by methods based on the number of observations and the censorship percentage over substitution methods for more precise estimations of environmental data with a high percentage of left-censored data. Water collectors adjacent to intensive-husbandry facilities, placed in direct runoffs from animal excreta, or in wastewater emissions contained median concentrations of MON and SAL approximately 70 times higher than those found in regional tributaries and main courses of 5 sub-basins of the pampas and mesopotamic regions, thus exhibiting a relevance to other similar agricultural pollutants widely reported as pesticides. Chemical speciation of these compounds in surface water was characterized especially for MON and SAL, where the pH and chemical oxygen demand of the natural water body was associated with the concentration of the soluble fraction. The concentrations in abundant rivers such as the Gualeguay deliver a contribution to a natural wetland such as the Paraná-River delta, which registered only one sample with a [MON] ≤ the limit of quantification. Since wetlands possess a limited removal capability, these affluent contributions recorded strongly indicate that attention must be paid to the development of guidelines involving quality criteria for assessing the impact of ionophore antibiotics on such ecosystems. Graphical abstract: Unlabelled Image Highlights: Ionophore antibiotics (IPAs) were quantified in rivers and wetlands from Argentina. MON was the most frequently detected in surface waters, and at higher concentrations. Concentrations of MON exhibited significant associations to waters pH and COD. The Paraná-River delta was a successful depuration system for IPAs at studied period.